A Rare Pediatric Case of Severe Rhabdomyolysis Owing to Dual Infection - Akıncı Göktaş, Özben; Bektaş, Ömer; Öz Tunçer, Gökçen; Birsin Özçakar, Zeynep; Talim, Beril; Tuba Eminoğlu, Fatma; Teber, Serap (Klinische Pädiatrie, 2021)
Aim We aimed to report a severe and rare pediatric rhabdomyolysis case associated with a dual viral infection.Case A 13 year-old, healthy girl presented with the complaints of fever, abdominal pain, weakness and dark-colored urine. She was diagnosed with rhabdomyolysis based on clinical signs and laboratory findings. The diagnosis was confirmed by serological tests and real-time polymerase chain reaction for Epstein-Barr virus (EBV) and cytomegalovirus (CMV), respectively. Other potential genetic, metabolic and infectious causes were evaluated meticulously but no evidence was found. This case is also important as it is the first reported case to our knowledge on rhabdomyolysis associated with EBV and CMV co-infection in children.Conclusion The presented case experienced tetraplegia due to the severe muscular damage and muscle power returned to normal range after 3 months. This suggests that EBV and CMV may have exert synergistic effects leading to more severe inflammation and degeneration.
Keywords: Rhabdomyolysis; Childhood; Epstein-Barr virus (EBV); Cytomegalovirus (CMV); Dual Infection